A biorefining process: Sequential, combinational lignocellulose pretreatment procedure for improving biobutanol production from sugarcane bagasse. (July 2015) - Su, Haifeng; Liu, Gang; He, Mingxiong; Tan, Furong
Highlights: A biorefining process: SCLPP was designed to pretreat lignocellulose. Improving biobutanol production from sugarcane bagasse. Enzymatic hydrolysis with simultaneous saccharification fermentation was effective. Developing SCLPP that increase biofuel from lignocellulose is feasible. Abstract: Here, for the first time, we designed a sequential, combinatorial lignocellulose pretreatment procedure (SCLPP) for microbial biofuel fermentation to reduce generation of microbial growth inhibitors and furthermore increase sugar yields. We tested this pretreatment process using sugarcane bagasse as substrate and assessed the effectiveness by analysis of biobutanol production through microbial clostridium beijerinckii NCIMB 8052 conversion. Our results showed that there were no inhibitory effects when using the hydrolysates as fermentation substrate. Under the SSF scheme, we observed the highest concentrations of butanol (6.4 g/L) and total ABE (11.9 g/L), resulting in a higher ABE productivity, compared with the SHF method. These findings suggest that the SCLPP is a feasible method for improving ABE production, lowering microbial inhibitor generation, and ensuring success in the subsequent fermentation process. Therefore, our work demonstrated developing a tractable integrated process that facilitates to increase biofuel production from agricultural residues rich in lignocellulose is feasible.